Evaluation of L-cell activity in the small intestine according to the extension of the biliopancreatic loop in patients undergoing Roux-en-Y gastric by-pass - Estabile, Priscila Costa (2025)
Background: Individuals with severe obesity and type 2 diabetes mellitus have reduced secretion of incretins by L cells. Studies suggest an increase in L cell activity according to the length of the Biliopancreatic Loop (BPL). Objective: Compare the effect of biliopancreatic loop extension on the number and expression of L cells in patients undergoing RYGB Methods: Subjects (n = 13) undergoing RYGB with a BPL of 100 cm (G1) or 200 cm (G2). Intestinal biopsies were done before (T1) and 6 months after (T2) RYGB in 3 segments: gastro-enteric anastomosis (A), entero-enteric anastomosis (B) and terminal ileum (C). Analyzes of intestinal biopsies by immunohistochemistry and qRT-PCR. Results: There was an increase (p < 0.0001) in L cells marked by PYY and GLP1 between T1 (17 ± 10.5) and T2 (23.5 ± 10.7) only at point C. There was no difference in L cells expression between groups G1 and G2 at points A (A1: 17.3 ± 2.9; A2: 19.9 ± 1.9; p = 0.09), B (B1: 13.7 ± 6.6; B2: 14.1 ± 4.9; p = 0.89) and C (C1: 13.2 ± 2.2; C2: 11.4 ± 3.4; p = 0.32) in PYY and GLP1 gene expression (A1: 20.8 ± 4, 1; A2: 23.7 ± 3.6; p = 0.2), B (B1:14.3 ± 7.9; B2: 22.7 ± 11.8; p = 0.1), (C1: 17±4.1; C2: 21.1 ± 4.8; p = 0.2). Conclusions: Both techniques lead to an increase in the number of active L cells.